Disodium Fumarate Alleviates Endoplasmic Reticulum Stress, Mitochondrial Damage, and Oxidative Stress Induced by the High-Concentrate Diet in the Mammary Gland Tissue of Hu Sheep - Meijuan Meng; Xu Zhao; Ran Huo; Xuerui Li; Guangjun Chang; Xiangzhen Shen (MDPI AG, 2023)
The long-term feeding of the high-concentrate diet (HC) reduced rumen pH and induced subacute rumen acidosis (SARA), leading to mammary gland tissue damage among ruminants. Disodium fumarate enhanced rumen bufferation and alleviated a decrease in rumen pH induced by the HC diet. Therefore, the purpose of this study was to investigate whether disodium fumarate could alleviate endoplasmic reticulum (ER) stress, mitochondrial damage, and oxidative stress induced by the high-concentrate diet in the mammary gland tissue of Hu sheep. In this study, 18 Hu sheep in mid-lactation were randomly divided into three groups: one fed with a low-concentrate diet (LC) diet, one fed with a HC diet, and one fed with a HC diet with disodium fumarate (AHC). Each sheep was given an additional 10 g of disodium fumarate/day. The experiment lasted for eight weeks. After the experiment, rumen fluid, blood, and mammary gland tissue were collected. The results show that, compared with the LC diet, the HC diet could reduce rumen pH, and the pH below 5.6 was more than 3 h, and the LPS content of blood and rumen fluid in HC the diet was significantly higher than in the LC diet. This indicates that the HC diet induced SARA in Hu sheep. However, the supplementation of disodium fumarate in the HC diet increased the rumen pH and decreased the content of LPS in blood and rumen fluid. Compared with the LC diet, the HC diet increased Ca2+ content in mammary gland tissue. However, the AHC diet decreased Ca2+ content. The HC diet induced ER stress in mammary gland tissue by increasing the mRNA and protein expressions of GRP78, CHOP, PERK, ATF6, and IRE1α. The HC diet also activated the IP3R-VDAC1-MCU channel and lead to mitochondrial damage by inhibiting mitochondrial fusion and promoting mitochondrial division, while disodium fumarate could alleviate these changes. In addition, disodium fumarate alleviated oxidative stress induced by the HC diet by activating Nrf2 signaling and reducing ROS production in mammary gland tissue. In conclusion, the supplementation of disodium fumarate at a daily dose of 10 g/sheep enhanced rumen bufferation by maintaining the ruminal pH above 6 and reduced LPS concentration in ruminal fluid and blood. This reaction avoided the negative effect observed by non-supplemented sheep that were fed with a high-concentrate diet involving endoplasmic reticulum stress, oxidative stress, and mitochondrial damage in the mammary gland tissue of Hu sheep.